Gramsci at Sea - Chari, Sharad (Forerunners: Ideas First, 2023)
pHow might an oceanic Gramsci speak to Black aquafuturism and other forms of oceanic critique? This succinct work reads Antonio Gramsci's writings on the sea, focused in his prison notes on waves of imperial power in the inter-war oceans of his time. Sharad Chari argues that the imprisoned militant's method is oceanic in form, and that this oceanic Marxism can attend to the roil of sociocultural dynamics, to waves of imperial power, as well as to the capacity of Black, Drexciyan, and other forms of oceanic critique to "storm" us on different shores./p